Introduction à la syntaxe de l’ « adverbe généralisé » en polonais - Kaliska, Agnieszka Kornelia (Studia Romanica Posnaniensia, 2012)
The purpose of the present research is to consider whether a syntactic approach proposed by Maurice Gross in "Syntaxe de l’adverbe" (1986) may prove helpful in analyzing Polish adverbs. The term of generalized adverb, proposed by M. Gross, is used for syntactically different structures (underived and derived adverbs, adverbials or adverbial subordinate clauses). In this paper we aim to present the basis for the delineation of morphological types of compound (frozen) adverbs in Polish which are classified according to their internal syntactic structure.